Magnons and magnetic fluctuations in atomically thin MnBi2Te4 - Lujan, David; Choe, Jeongheon; Rodriguez-Vega, Martin; Ye, Zhipeng; Leonardo, Aritz; Nunley, T. Nathan; Chang, Liang-Juan; Lee, Shang-Fan; Yan, Jiaqiang; Fiete, Gregory A.; He, Rui; Li, Xiaoqin (Nature communications, 2022)
Electron band topology is combined with intrinsic magnetic orders in MnBi 2 Te 4 , leading to novel quantum phases. Here we investigate collective spin excitations (i.e. magnons) and spin fluctuations in atomically thin MnBi 2 Te 4 flakes using Raman spectroscopy. In a two-septuple layer with non-trivial topology, magnon characteristics evolve as an external magnetic field tunes the ground state through three ordered phases: antiferromagnet, canted antiferromagnet, and ferromagnet. The Raman selection rules are determined by both the crystal symmetry and magnetic order while the magnon energy is determined by different interaction terms. Using non-interacting spin-wave theory, we extract the spin-wave gap at zero magnetic field, an anisotropy energy, and interlayer exchange in bilayers. We also find magnetic fluctuations increase with reduced thickness, which may contribute to a less robust magnetic order in single layers. MnBi2Te4, referred to as MBT, is a van der Waals material combining topological electron bands with magnetic order. Here, Lujan et al study collective spin excitations in MBT, and show that magnetic fluctuations increase as samples reduce in thickness, implying less robust magnetic order.